C and E, I believe since the other theorems don’t exist and AAS does not apply
To find is out put it like this 2 8
5 x
you multiple so 2 times what eduals 8 then you take that and multiply by 5
f(h(x))= 2x -21
Step-by-step explanation:
f(x)= x^3 - 6
h(x)=\sqrt[3]{2x-15}
WE need to find f(h(x)), use composition of functions
Plug in h(x)
f(h(x))=f(\sqrt[3]{2x-15})
Now we plug in f(x) in f(x)
f(h(x))=f(\sqrt[3]{2x-15})=(\sqrt[3]{2x-15})^3 - 6
cube and cube root will get cancelled
f(h(x))= 2x-15 -6= 2 x-21
Answer:
x=12
Step-by-step explanation:
9x-14=2(3x+11)
9x-14=6x+22
9x-6x=22+14
3x=36
x=36/3=12
Quotient means division
-36/-4 + 9 = x
9 + 9 = x
18 = x